2011
DOI: 10.1128/jcm.01961-10
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Flow Cytometry for Measurements of Plasmodium falciparum Parasite Burden in Studies in Areas of Malaria Endemicity by Use of Bidimensional Assessment of YOYO-1 and Autofluorescence

Abstract: The detection and quantification of Plasmodium falciparum in studies of malaria endemicity primarily relies upon microscopy. High-throughput quantitative methods with less subjectivity and greater reliability are needed for investigational studies. The staining of parasitized erythrocytes with YOYO-1 for flow cytometry bears great potential as a tool for assessing malaria parasite burden. Capillary blood was collected from children presenting to the pediatric ward of the Manhiça District Hospital in Mozambique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Further, hemozoin-containing monocytes observed by microscopy may provide insight regarding the total body parasite burden, as these cells do not sequester in P. falciparum infections [49,50]. Flow cytometric devices may also contribute new approaches for malaria diagnosis with emphasis on field deployment, however, further development of instrumentation is required [51][52][53][54][55]; limitations of speciesspecific detection must be acknowledged for flow cytometry.…”
Section: Microscopy and Cytometrymentioning
confidence: 98%
“…Further, hemozoin-containing monocytes observed by microscopy may provide insight regarding the total body parasite burden, as these cells do not sequester in P. falciparum infections [49,50]. Flow cytometric devices may also contribute new approaches for malaria diagnosis with emphasis on field deployment, however, further development of instrumentation is required [51][52][53][54][55]; limitations of speciesspecific detection must be acknowledged for flow cytometry.…”
Section: Microscopy and Cytometrymentioning
confidence: 98%
“…A comparison between microscopic analysis following Giemsa staining and FCM shows a very similar distribution (Fig. 1D) (14,23,24), YOYO-1 presented an excellent discrimination between uninfected and infected RBCs and was able to discriminate between mononucleated and multinucleated stages with high resolution. The fluorescence intensities of multinucleated-stage parasites (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Different dyes such as acridine orange (17,18), hydroethidine (19,20), SYTO 16 (21) and thiazole orange (22) were already employed for the determination of parasitemia in cultures of P. falciparum by FCM. Some previous studies using YOYO-1 showed that this dye possesses high affinity for DNA and discriminates infected RBC from the uninfected cells in a very effective way (14,23,24). Melatonin and derivatives mediating effects on the cell cycle of P. falciparum-infected human erythrocytes were studied using YOYO-1 staining followed by flow cytometry analysis.…”
mentioning
confidence: 99%
“…Cytometry of malaria-infected RBC has been used for (i) monitoring of infected RBC, mainly in mouse models (34)(35)(36)(37)(38)(39), (ii) characterization of infected RBC (15), (iii) assessment of maturation and/or viability of parasites in infected RBC (10,13,14,16,17,40,41), and (iv) to detect and count P. falciparum infected RBC in culture (14,(42)(43)(44) or from patient blood (45)(46)(47), with the possibility to distinguish species based on base composition (2,10,11).…”
Section: Malaria and Flow Cytometrymentioning
confidence: 99%